Organic Food Consumption During the Complementary Feeding Period and Respiratory or Allergic Diseases Up to Age 5.5 Years in the ELFE Cohort - Payet, David; Adjibade, Moufidath; Baudry, Julia; Ghozal, Manel; Camier, Aurore; Nicklaus, Sophie; Adel-Patient, Karine; Divaret-Chauveau, Amandine; Gauvreau-Béziat, Julie; Vin, Karine; Lioret, Sandrine; Charles, Marie Aline; et al. (Frontiers in Nutrition, 2021)
Objectives. To assess 1) whether a history of allergy is associated with feeding with organic foods (OF) during the complementary feeding period and 2) whether OF consumption in infancy is related to the incidence of respiratory and allergic diseases up to age 5.5 years. Study design. Analyses involved more than 8000 children from the nationwide ELFE birth cohort. Associations between family or infant history of allergy and frequency of OF consumption during the complementary feeding period were assessed with multinomial logistic regression. Associations between OF consumption in infancy and respiratory or allergic diseases between age 1 and 5.5 years were assessed with logistic regression. Results. A family history of allergy or cow’s milk protein allergy at age 2 months was strongly and positively related to feeding with OF during the complementary feeding period. Feeding with OF during the complementary feeding period was not related to respiratory diseases or eczema up to age 5.5 years. Compared to infrequent consumption of both organic and commercial complementary foods, frequent OF consumption without commercial complementary foods was associated with a higher risk of food allergy, whereas frequent commercial complementary foods consumption without OF use was associated with a lower risk of food allergy. Conclusions. This study suggests that a history of allergy strongly affects feeding with OF during the complementary feeding period. However, OF consumption was not associated with reduced odds of food allergy later in childhood but could be associated with increased odds, which should be examined more deeply.